Selfishness in the Individuals and Culture of Corruption: Theoretical Lens in Nepal’s Empirical Cases - Khanal, Shreedhar (NPRC Journal of Multidisciplinary Research, 2025)
Power, a fundamental element in political analysis, is under scrutiny in this paper. Disruptions in power distribution or leader selection can cause both immediate and prolonged harm to the system. With this premise, this paper investigates the philosophical foundations underlying the emergence and expansion of self-serving actors and their significant influence on Nepal’s governance system. Drawing from official data from secondary sources, the study tests the hypothesis that Nepal’s governance is controlled by self-serving individuals through the coefficient of determination (R²) analysis of relevant variables. While actors play vital roles, power itself remains intangible. The primary objective in power contests is the acquisition of resources. Favorable circumstances during these struggles often foster the development of self-interested individuals who become deeply embedded within the system. The research further concludes that the Nepali political system effectively facilitates the growth of selfish individuals, underscoring the urgency of the issue.